Pensamento computacional com a educação on-line no ensino médio integrado - Santos Júnior, Gilson Pereira dos (2023)
Debate about the inclusion of computational thinking in the education curricula of children and teenagers is growing worldwide, justified as a towards the transformations of a society that evolves with the digital world. In Brazil, mentions in the National Common Curriculum Baseline, in 2018, included the topic in elementary and secondary education. Amidst such changes in education, the health emergency of the covid-19 pandemic caused the suspension of presential educational activities. In view of the events, the objective of this thesis was to understand the non-presential development of computational thinking with online education in high school, considering the digital cultures of learners. I conducted the research in the light of the epistemological assumptions of multi-referentiality, within the scope of a research with the method of research-training method in cyberculture. This research was carried out with students of the high school technical training of Computer Networks who were taking the of the class of Introduction to Algorithms at the Instituto Federal de Sergipe, Lagarto Campus, in synchronous and asynchronous encounters, over the school years of 2020 and 2021. To obtain data, I combined the research diary app to the text and video records of synchronous meetings with the classes on Google Meet; the artifacts authored by the learners (hypertext and audiovisual documents, programming projects and web portfolio); and semi-structured interviews and traces of actions and interactions with students in digital interfaces and applications, such as Google Classroom, Whatsapp and Scratch. After immersion in the field, three subsuming notions emerged: playfulness as one of the principles of online education; authoring with computational thinking in online education; and collaborative creative learning with digital cultures. In this sense, the students' experiences and reports showed the potential of developing computational thinking with the principles of online education in non-presential practices, through the creation of open and interactive didactic designs that include, in addition to these, ludicity. Ludic and sensible welcoming, musical moments, as well as the aesthetics and contextualization of teaching materials inspired by the digital cultures of learners were devices created to make learning light, fun, interesting and meaningful, that contributed to overcoming the emotional challenges faced throughout the pandemic. In addition to that, the students' projects and their speeches highlighted how collaboration and the process of imagining, creating, playing, sharing, and reflecting were present in their strategies during the production of online authorship. They learned through experience, that is, creating, doing, researching, exploring, playing, making mistakes, with materials, with each other and with digital networks. Understanding knowledge as an “open-work”, listening to and getting to know the learners, and promoting authorial activities and learning situations inspired by digital cultures, interests, and their daily lives, steered the course to social and civic discussions, in addition to the technical aspects of the curriculum. For all the findings listed, from a look at online education, this thesis contributes with other ways of thinking-doing the development of computational thinking in the field of education, computing and adjacent fields.